Does exercise improve glycaemic control in type 1 diabetes? A systematic review and meta-analysis. - Amy Kennedy; Krishnarajah Nirantharakumar; Myriam Chimen; Terence T Pang; Karla Hemming; Rob C Andrews; Parth Narendran (PLoS ONE)
Objective Whilst regular exercise is advocated for people with type 1 diabetes, the benefits of this therapy are poorly delineated. Our objective was to review the evidence for a glycaemic benefit of exercise in type 1 diabetes. Research design and methods Electronic database searches were carried out in MEDLINE, Embase, Cochrane's Controlled Trials Register and SPORTDiscus. In addition, we searched for as yet unpublished but completed trials. Glycaemic benefit was defined as an improvement in glycosylated haemoglobin (HbA1c). Both randomised and non-randomised controlled trials were included. Results Thirteen studies were identified in the systematic review. Meta-analysis of twelve of these (including 452 patients) demonstrated an HbA1c reduction but this was not statistically significant (standardised mean difference (SMD) -0.25; 95% CI, -0.59 to 0.09). Conclusions This meta-analysis does not reveal evidence for a glycaemic benefit of exercise as measured by HbA1c. Reasons for this finding could include increased calorie intake, insulin dose reductions around the time of exercise or lack of power. We also suggest that HbA1c may not be a sensitive indicator of glycaemic control, and that improvement in glycaemic variability may not be reflected in this measure. Exercise does however have other proven benefits in type 1 diabetes, and remains an important part of its management.